2021
DOI: 10.3389/fresc.2021.782848
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Osteo-Sarcopenia, and Musculoskeletal Mechano-Transduction

Abstract: The decline in the mass and function of bone and muscle is an inevitable consequence of healthy aging with early onset and accelerated decline in those with chronic disease. Termed osteo-sarcopenia, this condition predisposes the decreased activity, falls, low-energy fractures, and increased risk of co-morbid disease that leads to musculoskeletal frailty. The biology of osteo-sarcopenia is most understood in the context of systemic neuro-endocrine and immune/inflammatory alterations that drive inflammation, ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 187 publications
(201 reference statements)
0
2
0
Order By: Relevance
“…Like many other tissues, the skeleton follows a ‘use it or lose it’ model, wherein continued disuse leads to a cycle of wasting, decreased capacity, and fragility, especially in aging ( Leser et al, 2021 ), when the balance of deposition and resorption shifts towards net loss of mineralized bone. Bone mass and osteoblast number decrease with age ( Almeida, 2012 ), but study after study ( Layne and Nelson, 1999 ; Mosti et al, 2014 ; Watson et al, 2018 ; Holubiac et al, 2022 ) report the protective benefits of mechanical loading and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Like many other tissues, the skeleton follows a ‘use it or lose it’ model, wherein continued disuse leads to a cycle of wasting, decreased capacity, and fragility, especially in aging ( Leser et al, 2021 ), when the balance of deposition and resorption shifts towards net loss of mineralized bone. Bone mass and osteoblast number decrease with age ( Almeida, 2012 ), but study after study ( Layne and Nelson, 1999 ; Mosti et al, 2014 ; Watson et al, 2018 ; Holubiac et al, 2022 ) report the protective benefits of mechanical loading and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is considered a special form of senescence, but recent studies have found that some patients start to lose muscle mass in middle age or even youth ( 14–16 ). This type of sarcopenia that progresses in early-life is called early-onset sarcopenia ( 17–19 ). Early-onset sarcopenia has worse clinical manifestations and prognosis than ordinary sarcopenia ( 20 ).…”
Section: Introductionmentioning
confidence: 99%